Acute telogen effluvium triad after resolution, - Leticia Arsie Contin; Vanessa Barreto Rocha (Sociedade Brasileira de Dermatologia, 2021)
Abstract Five cases of telogen effluvium undergoing resolution are shown, with the presence of frontal, bitemporal, and occipital hair regrowth. Diagnosing acute telogen effluvium after the end of the active phase can be challenging, especially when the pull test is negative. The differential diagnosis includes alopecia areata and traction alopecia. Clinical signs of hair regrowth after telogen effluvium can help in the diagnosis. The frontal and temporal areas have more telogen hairs and are more affected. On the occipital area, hairs seem to have the same behavior. The acute telogen effluvium triad during resolution is proposed: frontal fringe, temporal recess and occipital fringe.